Revolutionizing History Learning in The Digital Era: Transforming the Way We Learn - Marpelina, Leni; ., Sariyatun; ., Andayani (KnE Social Sciences, 2024)
The emergence of digital technology in the Industry 4.0 era has ushered in significant changes and influenced various aspects of human life, including education. Considering the pursuit sustainable progress, it’s imperative for education must effectively utilize Information and Communication Technology (ICT) to elevate its standards, particularly in the domain of history instruction. This investigation underscores the theme of innovation and evolution in history teaching, particularly amid the digital age. The phrase “revolutionizing” connotes the transformative alterations being advocated, while “redefining our learning methods” lucidly sets forth the study’s aim. This inquiry underscores the redefinition and modernization of history pedagogy in the age of digital advancements, encapsulating the envisioned outcomes. The research methodology is driven by a qualitative descriptive approach. Data is amassed through a comprehensive examination of diverse reports, academic articles, and online platforms. Results suggest that contemporary history instruction in the digital epoch prominently features resources in tune with ongoing technological and internet progressions. The pedagogical strategy champions an unbounded educational setting, fostering learning at any place and time. Educational tools in the classroom have pivoted from traditional mediums to multimedia channels, encompassing e-books, virtual reality, augmented reality, mixed reality, Admodo, social platforms, YouTube, podcasts, and more. Consequently, history educators are compelled to shift the conventional, often tedious image of history lessons to more interactive and invigorating educational ventures. The commitment and proactive role of history educators become pivotal in realizing optimal history teaching in the 4.0 era. Keywords: Revolutionizing, history learning, digital era